FAITH IN THE MARKETPLACE: HOW AMANAH SHAPES SOCIAL TRUST AND CONSUMER LOYALTY AMONG MUSLIM SMES IN INDONESIA - Besse Faradiba; Ida Ilmiah Mursidin; Damirah; Aulia Nur Irsha (Academic Bright Collaboration, 2026)
This study aims to analyze the sociological role of Amanah (trustworthiness) as a spiritual-social foundation in Islamic SMEs and how it bridges the gap between formal management strategies, product quality, and consumer loyalty. It specifically investigates the potential paradox where religious ethics might interact unpredictably with modern management practices. A quantitative approach was employed utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. Data were gathered via a structured survey involving 313 respondents, comprising active consumers and business practitioners of Islamic SMEs in Makassar, Indonesia. The results reveal that while management strategy and product quality significantly and positively influence loyalty, a striking paradox emerges: Amanah shows a significant negative moderation effect on the relationship between management strategy and consumer loyalty. This suggests that over-reliance on formal management may diminish the organic trust-building power of religious ethics. However, Amanah remains a full mediator that converts product quality into long-term loyalty. The findings suggest that